An Autobiography : The Story of My Experiments with Truth - Gandhi,Mahatma (Newdelhi : Classics, 2015)
In the mid-1920s, prompted by a "small, still voice" that encouraged him to lay bare what was known only to him and his God, M. K. Gandhi began writing and publishing his autobiography. Drafted during a period of intensive fasting and "in-dwelling" at his ashram in Ahmedabad, his story of the soul portrayed the deeper, more inward experiences that made him externally an innovator in the struggles against violence, racism, and colonialism. The book, written in Gujarati and translated into English by Mahadev Desai, would become an international classic, hailed as one of the "100 Best Spiritual Books of the 20th Century." This first critical edition of this seminal work by leading Gandhi scholar Tridip Suhrud offers an unprecedented window into the original Gujarati text. Including both alternative English translations and illuminating notes, as well as a deeply researched introduction, it will bring renewed critical attention to one of the world's most widely read books.
Keywords: Autobiography